ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI SIKAP DAN PERILAKU PESERTA DIDIK KELAS V DALAM MENGAMALKAN NILAI PANCASILA DI SEKOLAH DASAR - Thoyyibatu Diniyah; Ahmad Hariandi; Muhammad Sholeh (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the gap between students’ understanding of Pancasila values and their actual behavior in daily school life. Students are generally able to memorize the principles of Pancasila, but have not fully implemented them in attitudes and behavior. This study aims to analyze internal factors influencing the attitudes and behavior of fifth-grade students in practicing Pancasila values in elementary school and to describe the forms of implementation. This study used a qualitative descriptive approach. The research was conducted at SDN 133/I Pasar Terusan. Data were collected through observation, interviews, and documentation. Data analysis techniques included data reduction, data display, and conclusion drawing. The results showed that internal factors influencing the practice of Pancasila values include self-awareness, intrinsic motivation, understanding of values, and self-control. The forms of practicing Pancasila values were reflected in cooperation, social care, discipline, responsibility, and respect for others’ opinions. However, these practices were not consistently carried out by all students. Therefore, internal factors play an important role in shaping students’ attitudes and behavior in practicing Pancasila values.